2005
DOI: 10.1523/jneurosci.3825-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Stimulus Interactions within Single Response Fields of Superior Colliculus Neurons

Abstract: In addition to its role in saccade generation, the superior colliculus (SC) is involved in target selection, saccade selection, and shifting the focus of spatial attention. Here, we investigated the influence of saccade selection on sensory interactions within single response fields (RFs) of SC neurons. One or two differently shaped stimuli were presented within single RFs of SC neurons, and the shape of a centrally located cue indicated whether and where to make a saccade (Go-Go) or whether to make or withhol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 113 publications
(111 reference statements)
6
61
0
1
Order By: Relevance
“…Similarly, it has been reported that the product of within-modal visual interactions in cortical visual neurons is in most cases subadditive (Movshon et al, 1978;Henry et al, 1978, Britten andHeuer, 1999;Carandini et al, 1997;Reynolds et al, 1999;Gawne and Martin, 2002;Lampl et al, 2004;Li and Basso, 2005). These observations prompt the search for more appropriate models to describe the products of unisensory integration.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, it has been reported that the product of within-modal visual interactions in cortical visual neurons is in most cases subadditive (Movshon et al, 1978;Henry et al, 1978, Britten andHeuer, 1999;Carandini et al, 1997;Reynolds et al, 1999;Gawne and Martin, 2002;Lampl et al, 2004;Li and Basso, 2005). These observations prompt the search for more appropriate models to describe the products of unisensory integration.…”
Section: Discussionmentioning
confidence: 88%
“…For electrophysiological recording of single neurons and monitoring eye movements, cylinders and eye movement measuring loops were implanted in two rhesus monkeys (Macaca mulatta) using procedures described previously (Li and Basso, 2005). All experimental protocols were approved by the University of WisconsinMadison Institutional Animal Care and Use Committee and complied with or exceeded standards set by the Public Health Service policy on the humane care and use of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%
“…We used a real-time experimental data acquisition and visual stimulus generation system (Tempo and VideoSync; Reflective Computing, Olympia, WA) to create the behavioral paradigms and acquire eye position and single neuron data as described previously (Li and Basso, 2005;Li et al, 2006). Visual stimuli appeared on a display with a native resolution of 1024 ϫ 768, operating at 60 Hz and located at 51 cm distance from the monkey.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Alvarado et al (2007) provided evidence for suppressive interactions between withinmodal pairs suggestive of competitive rather than reinforcing effects of excitatory pairs from the same modality. As they note, mutual antagonism, even for visual stimuli restricted to the same receptive field, could aid in selecting among potential goals for an orienting movement (Li and Basso, 2005). However, cues from different senses that occur in close spatial and temporal coincidence are likely derived from a singular event.…”
Section: Cortico-sc Influence On Integration Is Multisensory-specificmentioning
confidence: 99%